Peran Pondok Pesantren Annida Al Islamy Dalam Perkembangan Pendidikan Islam Di Bekasi Tahun 1963-1980 - Mawadah*, Dina; Fadillah, Moh Ali; Nurhasanah, Ana (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
Islamic boarding schools are the oldest Islamic educational institutions in Indonesia. Islamic boarding schools were born out of the awareness and obligation to teach Islamic religion and at the same time hope to produce prospective ulama. The purpose of this study is: (1) Knowing the process of establishing the Annida Al Islamy guest house, (2) Knowing the development of the Annida Al Islamy guest house in 1963-1980, (3) knowing the effect of Annida Al Islamy guest house on Islamic education in Bekasi. The study used historical methods consisting of heuristics, source criticism, interpretation and historiography. The results of the study show that the Annida Al Islamy pesantren was discovered by KH. Muhammad Emigran Amsar Addary in 1963. The establishment of the Annida Al Islamy pesantren by KH. Muhammad Emigran was based on the interests of the people, to instill the foundations of Islam at all levels of society. Based on the needs of his students, KH. Muhammad Muhajirajir tried to level things with the government so that Annida pesantren would be equivalent to other pesantrens. Finally in 1980, the Annida pesantren was closed to meet this requirement and made the Annida pesantren a modern pesantren. After this development, facilities and infrastructure that support learning for students continued to be improved, classroom was built for the Tsanawiyah and Aliyah madrasas and the Annida Islamic boarding school built the Al-Marhala Al-Ulya Campus for students who had completed their education.Keywords: History, Annida Al-Islam Islamic Islamic boarding school, Development